2017
DOI: 10.1108/ecam-06-2015-0101
|View full text |Cite
|
Sign up to set email alerts
|

Designers’ performance evaluation in construction projects

Abstract: Purpose In a construction project, “participants’ satisfaction” is one of the main dimensions used for measuring the successfulness of a project. Designers perform a major role in attaining the project goals and managing project complexity during production. The purpose of this paper is to examine the designers’ performance as evaluated by the main participants: the client, the project consultant/manager and the main contractor, and to identify the main success factors of designer performance using the partici… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
27
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 33 publications
(27 citation statements)
references
References 45 publications
0
27
0
Order By: Relevance
“…The factors that influence the performance of architects can be classified into i) working condition (Sinesilassie Tabish and Jha, 2017;Böckerman and Ilmakunnas, 2019), ii) organisational support (Young and Young, 2012;Lai, Yusof and Kamal, 2016), iii) working relationship (Kärnä and Junnonen, 2017;Afolabi et al, 2018) and iv) design process (Kärnä and Junnonen, 2017;Assaf, Hassanain and Abdallah, 2018;Othman and Elsaay, 2018). These factors are subsequently discussed in detail.…”
Section: Factors Influencing the Performance Of Architectsmentioning
confidence: 99%
See 4 more Smart Citations
“…The factors that influence the performance of architects can be classified into i) working condition (Sinesilassie Tabish and Jha, 2017;Böckerman and Ilmakunnas, 2019), ii) organisational support (Young and Young, 2012;Lai, Yusof and Kamal, 2016), iii) working relationship (Kärnä and Junnonen, 2017;Afolabi et al, 2018) and iv) design process (Kärnä and Junnonen, 2017;Assaf, Hassanain and Abdallah, 2018;Othman and Elsaay, 2018). These factors are subsequently discussed in detail.…”
Section: Factors Influencing the Performance Of Architectsmentioning
confidence: 99%
“…In particular, the construction industry has been recognised to experience loss due to reworks, delays, defects and several other reasons involving professionals in the industry (Nawi et al, 2009;Hamza et al, 2019). Several scholars have argued that these problems are partly because of mistakes in design decisions (Nawi et al, 2009;Kärnä and Junnonen, 2017) and deficiencies in the design documents (Abdallah, Assaf and Hassanain, 2019); thus, architects have been indicted to be responsible for errors, which occur in buildings. Nawi et al (2009) investigated the constructability concept in Malaysia and found that challenges such as delays and reworks are aggravated by the weaknesses of the designs produced by architects at the design stage.…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations